1980
DOI: 10.1093/jat/4.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Purification and Stability: Requirements for a Metabolism Study of an Azo Dye and Pigment

Abstract: Impurities of aromatic amines in the azo dye and pigment, Direct Black 38 and Pigment Yellow 12, and in vitro stability of the dye were determined. These factors can affect the results of studies designed to ascertain whether the two compounds are metabolized to potential carcinogens in hamsters. Procedures for removing impurities from the two compounds are also presented. Electron-capture gas chromatography of the heptafluorobutyryl derivatives of the impurities and degradation products was used to satisfy al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Besides the possible toxicity of azo dyes per se [Yadav et al, ; Fernandes et al, ], these dyes can also present hazards mediated by their constituent aromatic amines. Residues of the amines used in synthesis may remain as impurities in the final dye product [Stavric et al, ; Nony and Bowman, ]. Furthermore, the aromatic amine components of the dyes may be liberated by the action of azoreductases, which can split the azo bond [Prival et al, ; Prival et al, ; Ryan et al, ; Feng et al, ; Mercier et al, ; Brissos et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the possible toxicity of azo dyes per se [Yadav et al, ; Fernandes et al, ], these dyes can also present hazards mediated by their constituent aromatic amines. Residues of the amines used in synthesis may remain as impurities in the final dye product [Stavric et al, ; Nony and Bowman, ]. Furthermore, the aromatic amine components of the dyes may be liberated by the action of azoreductases, which can split the azo bond [Prival et al, ; Prival et al, ; Ryan et al, ; Feng et al, ; Mercier et al, ; Brissos et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes were technical grade (percent purity is reported as available) and were purchased from Sigma-Aldrich (fast yellow AB 95% purity, congo red 91% purity), Acros (acid red 27 85% purity, metanil yellow 98% purity, methyl red, acid orange 7, acid yellow 11, acid yellow 17), Alfar-Aesar (methyl orange) or TCI (eriochrome black T). The primary impurities in azo dyes are their parent amines, based on study of direct black 38 and pigment yellow 12 ; small amounts of dispersants (e.g., polymers, surfactants) are also likely. We will show that amines of the azo dye MO do not affect reaction rate enhancement.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that there is a strong relationship between exposure to aromatic amines and risk to human cancer [1]. Since dyes have a high degree of chemical and photolytic stability [2] adsorption can be regarded as an appropriate method for dye removal prior their release into rivers, lakes etc. [3,4].…”
Section: Introductionmentioning
confidence: 99%